"She told me no, that you cannot change": Understanding provider refusal to remove contraceptive implants - Leigh Senderowicz; Al Kolenda (Elsevier, 2022)
Enthusiasm for long-acting reversible contraception (LARC) is growing among donors and NGOs throughout the global reproductive health field. There is an emerging concern, however, that the push to insert these methods has not been accompanied by a commensurate push for access to method removal. We use data from 17 focus group discussions with women of reproductive age in an anonymized African setting to understand how users approach providers to request method removal, and how they understand whether or not such a request will be granted. Focus group participants described how providers took on a gatekeeping role to removal services, adjudicating which requests for LARC removal they deemed legitimate enough to be granted. Participants reported that providers often did not consider a simple desire to discontinue the method to be a good enough reason to remove LARC, nor the experience of painful side-effects. Respondents discussed the deployment of what we call legitimating practices, in which they marshalled social support, medical evidence, and other resources to convince providers that their request for removal was indeed serious enough to be honored. This analysis examines the starkly gendered nature of contraceptive coercion, in which women are expected to bear the brunt of contraceptive side-effects, while men are expected to tolerate no inconvenience at all, even vicarious. This evidence of contraceptive coercion and medical misogyny demonstrates the need to center contraceptive autonomy not only at the time of method provision, but at the time of desired discontinuation as well.